Trends in measles incidence and measles vaccination coverage in Nigeria, 2008–2018. (17th November 2021) - Jean Baptiste, Anne Eudes; Masresha, Balcha; Wagai, John; Luce, Richard; Oteri, Joseph; Dieng, Boubacar; Bawa, Samuel; Ikeonu, Obianuju Caroline; Chukwuji, Martin; Braka, Fiona; Sanders, E.A.M.; Hahné, Susan; et al.
Abstract: Introduction: All WHO regions have set measles elimination objective for 2020. To address the specific needs of achieving measles elimination, Nigeria is using a strategy focusing on improving vaccination coverage with the first routine dose of (monovalent) measles (MCV1) at 9 months, providing measles vaccine through supplemental immunization activities (children 9–59 months), and intensified measles case-based surveillance system. Methods: We reviewed measles immunization coverage from population-based surveys conducted in 2010, 2013 and 2017–18. Additionally, we analyzed measles case-based surveillance reports from 2008–2018 to determine annual, regional and age-specific incidence rates. Findings: Survey results indicated low MCV1 coverage (54.0% in 2018); with lower coverage in the North (mean 45.5%). Of the 153, 097 confirmed cases reported over the studied period, 85.5% (130, 871) were from the North. Moreover, 70.8% (108, 310) of the confirmed cases were unvaccinated. Annual measles incidence varied from a high of 320.39 per 1, 000, 000 population in 2013 to a low of 9.80 per 1, 000, 000 in 2009. The incidence rate is higher among the 9–11 months (524.0 per million) and 12–59 months (376.0 per million). Between 2008 and 2018, the incidence rate had showed geographical variation, with higher incidence in the North (70.6 per million) compare to the South (17.8 per million). Conclusion: The aim of this study was to provide a descriptive analysis of measles vaccine coverage and incidence in Nigeria from 2008 to 2018 to assess country progress towards measles elimination. Although the total numbers of confirmed measles cases had decreased over the time period, measles routine coverage remains sub-optimal, and the incidence rates are critically high. The high burden of measles in the North highlight the need for region-specific interventions. The measles program relies heavily on polio resources. As the polio program winds down, strong commitments will be required to achieve elimination goals.